Electrical operation of electrostatic precipitators - Parker, K. R. (Institution of Engineering and Technology, 2003)
The book reviews developments in the following fields: electrostatic precipitator application; fundamental operation of an electrostatic precipitator; electrostatic precipitator design and performance; mechanical features impacting on electrical operation; electrical energisation equipment development; mains frequency energisation and control; alternative mains frequency energisation system; high frequency energisation system; electrical resistivity impact; online monitoring; and fault identification.